Soil and plant analysis : - Houba, V. J. G. (Wageningen Agricultural University, 1995)
This statement, chosen at the time as motto for the first edition of the present syllabus, is still valid. Up to now there is indeed no approach of soil testing that can be universally applied, and it is quesionable if there will ever be one.